2022
DOI: 10.1002/sd.2461
|View full text |Cite
|
Sign up to set email alerts
|

Success factors of global goal‐setting for sustainable development: Learning from the Millennium Development Goals

Abstract: The Millennium Development Goals (MDGs) were an important precursor to the Sustainable Development Goals (SDGs). Hence, identifying the conditions that made the MDGs successful enhances our understanding of global goal-setting and informs the global endeavour to achieve the SDGs. Drawing on a comprehensive review of 316 articles published between 2009 and 2018, we identify six factors that have enabled or hindered MDG implementation. Our analysis stresses the importance of path dependencies and shows that the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
25
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 27 publications
(25 citation statements)
references
References 125 publications
0
25
0
Order By: Relevance
“…Following agreement on the 2030 Agenda, the UN found that established partnerships had fallen far short of what was needed, merely ‘only scratching the surface’ in terms of the number, and quality, of partnerships required to deliver the SDGs (Stibbe and Prescott, 2022). Some of the difficulties are made clear in the widely cited review of research by Pattberg and Widerberg (2016) and a literature review by Hickman et al (2022). The Pattberg and Widerberg (2016) research recommended nine enhancements for partnership success to achieve the results expected of the Global Goals and their targets: An optimal partner mix Effective leadership Stringent goal-setting Sustained funding Professional process management Regular monitoring, reporting, and evaluation Active meta-governance Favourable political and social context Fit to problem-structure This increasingly professionalised approach to developing multi-stakeholder partnerships (MSPs), envisioned as necessary to their success, can also be seen as a contradiction to the underlying logic of SDG 17.…”
Section: Brief Conceptual History Of Sdg 17mentioning
confidence: 99%
See 1 more Smart Citation
“…Following agreement on the 2030 Agenda, the UN found that established partnerships had fallen far short of what was needed, merely ‘only scratching the surface’ in terms of the number, and quality, of partnerships required to deliver the SDGs (Stibbe and Prescott, 2022). Some of the difficulties are made clear in the widely cited review of research by Pattberg and Widerberg (2016) and a literature review by Hickman et al (2022). The Pattberg and Widerberg (2016) research recommended nine enhancements for partnership success to achieve the results expected of the Global Goals and their targets: An optimal partner mix Effective leadership Stringent goal-setting Sustained funding Professional process management Regular monitoring, reporting, and evaluation Active meta-governance Favourable political and social context Fit to problem-structure This increasingly professionalised approach to developing multi-stakeholder partnerships (MSPs), envisioned as necessary to their success, can also be seen as a contradiction to the underlying logic of SDG 17.…”
Section: Brief Conceptual History Of Sdg 17mentioning
confidence: 99%
“…On the other hand, it may be that professionalism is secondary to other factors. Hickman et al (2022) found that the Millennium Development Goals (MDGs), the precursor to the SDGs, catalysed changes only in countries with resource availability, administrative capacity, and economic development, which included support from external donors. With the commonalities in framework and institutional support between the MDGs and the SDGs this has serious implications for how the SDGs are approached in vulnerable areas like the tropics.…”
Section: Brief Conceptual History Of Sdg 17mentioning
confidence: 99%
“…The MDGs were the first comprehensive global governance framework to facilitate sustainable development introduced in 2000 as a set of goals enshrined in the United Nations Millennium Declaration to be achieved by 2015. They were the most elaborate attempt by the United Nations to guide development policies through globally defined policy goals up to that time (Hickmann et al, 2022). The MDGs were aimed at developing countries and contained eight main goals: eradicating poverty and hunger, achieving universal access to primary education, reducing child and maternal mortality and improving maternal health, promoting gender equality and empowering women, combating HIV / AIDS, malaria and other diseases, ensuring environmental sustainability and creating global partnership for development (UN General Assembly, 2015).…”
Section: Introductionmentioning
confidence: 99%
“…The concept of sustainable development began to gather momentum following the 1987 Brundtland Report and since then has become As the MDGs were one of the most ambitious initiatives ever presented, this popular topic also resulted in a large number of studies that have assessed MDGs' impact focusing on specific goals (Bisbee et al, 2019;Cha, 2017;Isola et al, 2015), countries (Balogun, 2019;Barimah & Diko, 2013) or attempting a comprehensive evaluation of MDGs' impacts (Halisçelik & Soytas, 2019;Hickmann et al, 2022;Lomazzi et al, 2014). Despite the rich literature on the MDGs, studies that deal specifically with international trade, which played an important role in the MDGs, were not published.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation